PENGARUH PEMUPUKAN ORGANIK DAN ANORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG PULUT (Zea mays ceratina) - Atslin Aryaningjannah; Dwi Retno Lukiwati; Sutarno Sutarno (Universitas Tribhuwana Tunggadewi, 2021)
Increasing the growth and production of waxy corn can be done by fertilizing. This study examined the effect of N-Leucaena leucocephala and P-rock phosphate enriched manure that was called manure plus, on the growth and production of waxy corn. The study used a randomized block design (RBD) with five treatments and six replicated namely T0 (urea + TSP), T1 (cow manure + urea + TSP), T2 (goat manure + urea + TSP), T3 (cow manure plus), and T4 (goat manure plus) with five treatments and six replicates. Parameters measured were plant height, leaves number, stem diameter, chlorophyll levels, waxy corn production, and dry matter production of stover. The results showed that stem diameter, chlorophyll, waxy corn production, and dry matter production of stover in cow manure plus and goat manure plus was equivalent to cow manure + urea + TSP and goat manure + urea + TSP, respectively. The number of leaves in the goat manure + urea + TSP treatment is higher compared to goat manure plus. However, plant height was not significantly affected by the treatments.